Metabolic syndrome in patients at a center of medical specialties in a small town of Bahia - Araújo, Cybele Sodré (2012)
Objetcive: To determine the prevalence of MS in individuals of both sexes, aged between 20 and 60 years, attending a Center of Medical Specialties interior of Bahia. Methodology: It is characterized in a descriptive study, with the population of 100 people, where 21 were included in the study. A questionnaire was used with data of lifestyle, weight, height, waist circumference (WC), lipid profile and glucose contained in the patient, presence of diabetes mellitus and hypertension. For the diagnosis of MS parameters used were the IDF, 2006. For statistical analysis we used the calculation of central tendency, standard deviation, Student t test and chi-square. Results: MS was observed in 71.43% of the subjects studied. The mean age was 43.6 years. With regard to the style and life, most do not drink, do not smoke and do physical activity. The components most relevant to MS were hypertension, hypertriglyceridemia and increased DC. Conclusion: The high prevalence of MS in this study suggests the intensified preventive health policies, with the key point to change lifestyle